Cordycepin inhibits colon cancer proliferation by suppressing MYC expression - Zhe Zhang; Kui Li; Zhi Zheng; Yu Liu (BMC, 2022)
Abstract Background Cordycepin is a purine nucleoside anti-metabolite and anti-biotic isolated from the fungus Cordyceps militaris, which has potential anti-neoplastic activities. This study aimed to investigate the effect of cordycepin in inhibiting colon cancer development. Methods The proliferation of cordycepin-treated HCT116 and Caco-2 colon cancer cell lines was assessed with 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and the viability was measured with colony formation assay. At the same time, cordycepin responsive gene and microRNAs (miRNAs, miRs) were screened by qRT-PCR. MYC over-expressing HCT116 and Caco-2 cell lines were constructed, which were further transfected with miR-26a. Inhibitory effect of cordycepin on cell proliferation was evaluated with cell viability assay, cell number count, and colony formation assay. The relative expression of MYC and miR-26a was detected by qRT-PCR and Western blot. Results Cordycepin inhibited colon cancer cell proliferation by down-regulating MYC mRNA/protein expression and up-regulating miR-26a in both HCT116 and Caco-2 cells. MYC over-expression could suppress the expression of miR-26a, which could be restored by cordycepin treatment. Additional miR-26a transfection in MYC over-expressing cells could reverse MYC over-expression-promoted proliferation, which could be further potentiated by cordycepin treatment. Conclusion Cordycepin is able to suppress colon cancer cell proliferation, likely mediated by the MYC/miR-26a pathway, supporting its potential for the treatment of colon cancer.